Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Vertical distribution of ionizing radiation and nano-aerosols in the austral troposphere and stratosphere with concurrent solar flare - Wendy D. Maxwell; Mohamad E. Alabdulkarim; Vibhor Thapliyal; Deanna C. Denton; Grace S. Maxwell; Hazel E. Maxwell; Iden D. Maxwell; Forrest J. Maxwell; Toen Castle; James L. Maxwell (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Dissociative-like Neurotoxicity Following Analytically Confirmed Exposure To Hexahydrocannabinol (HHC) - Shaun L. Greene; Rebecca Fawcett; Jared Castle; Zeff Koutsogiannis (Journal of Medical Toxicology, 2026)

Integrated biostratigraphy, chemostratigraphy and geochronology of the lower Cambrian succession in the western Stansbury Basin, South Australia - J. Castle-Jones; M. J. Betts; J. D. Holmes; R. M. Klaebe; P. A. Hall; J. L. Crowley; Z.-L. Zhang; G. A. Brock (Australian Journal of Earth Sciences, 2025)

P19-36 Dietary exposure assessment to plasticisers migrating from food contact materials - C. Cascio; G. Bubnyte; F.R. Mancini; M.D.F. Tavares Poças; R. Franz; E. Fabjan; S. Frattini; N. Hellsten; E. Stojanova; K. Baert; M. Georgiadis; G. Di Piazza; et al. (Toxicology Letters, 2024)

Barriers and Facilitators to a Healthy Community Environment During COVID-19: Perceptions of Extension Nutrition Educators and Other Key Community Stakeholders - E. Varela; J. Zeldman; A. Kuch; Y. Wang; M. Shushari; E. Hall; J. McNamara; J. Morrell; T. Tolar-Peterson; O. Brown; M. Olfert; L. Franzen-Castle; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Nebraska Double up Food Bucks - Prioritizing Partnerships for Food Access - V. Wielenga; L. Franzen-Castle (Journal of the Academy of Nutrition and Dietetics, 2023)

Stuck in the mud: Persistent failure of ‘the science’ to provide reliable information on the ecological roles of Australian dingoes - Geoff Castle; Malcolm S. Kennedy; Benjamin L. Allen (Biological Conservation, 2023)

Impacts of cover crops and nitrogen fertilization on agricultural soil fungal and bacterial communities - Sarah C. Castle; Deborah A. Samac; Jessica L. Gutknecht; Michael J. Sadowsky; Carl J. Rosen; Daniel Schlatter; Linda L. Kinkel (Plant and Soil, 2021)

Narrow range of temperature and irradiance supports optimal development of Lessonia corrugata (Ochrophyta) gametophytes: implications for kelp aquaculture and responses to climate change - Ellie R. Paine; Matthias Schmid; Juan Diego Gaitán-Espitia; Joshua Castle; Ian Jameson; John C. Sanderson; Catriona L. Hurd (Journal of Applied Phycology, 2021)

Photocatalysis of a Commercial Naphthenic Acid in Water Using Fixed-Film TiO2 - Andrew D. McQueen; Ciera M. Kinley; Rebecca L. Kiekhaefer; Alyssa J. Calomeni; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2016)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Model studies of migration from paper and board into fruit and vegetables and into Tenax™ as a food simulant - E.L. Bradley; L. Castle; D.R. Speck (Food Additives & Contaminants: Part A, 2014)

Safety evaluation of mechanical recycling processes used to produce polyethylene terephthalate (PET) intended for food contact applications - E. Barthélémy; D. Spyropoulos; M.-R. Milana; K. Pfaff; N. Gontard; E. Lampi; L. Castle (Food Additives & Contaminants: Part A, 2014)

Development of a new modelling tool (FACET) to assess exposure to chemical migrants from food packaging - P.K.T. Oldring; C. O’Mahony; J. Dixon; M. Vints; J. Mehegan; C. Dequatre; L. Castle (Food Additives & Contaminants: Part A, 2014)

Analytical screening studies on irradiated food packaging - M. Driffield; E.L. Bradley; I. Leon; L. Lister; D.R. Speck; L. Castle; E.L.J. Potter (Food Additives & Contaminants: Part A, 2014)

Estimates of dietary exposure to bisphenol A (BPA) from light metal packaging using food consumption and packaging usage data: a refined deterministic approach and a fully probabilistic (FACET) approach - P.K.T. Oldring; L. Castle; C. O’Mahony; J. Dixon (Food Additives & Contaminants: Part A, 2014)

Seasonal Performance of a Hybrid Pilot-Scale Constructed Wetland Treatment System for Simulated Fresh Oil Field-Produced Water - Bethany L. Alley; Ben Willis; John Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2013)

Printing ink compounds in foods: UK survey results - E.L. Bradley; J.S. Stratton; J. Leak; L. Lister; L. Castle (Food Additives & Contaminants Part B-Surveillance, 2013)

Exposure to phthalic acid, phthalate diesters and phthalate monoesters from foodstuffs: UK total diet study results - Emma L. Bradley; Richard A. Burden; Karim Bentayeb; Malcolm Driffield; Nick Harmer; David N. Mortimer; Dennis R. Speck; Jana Ticha; Laurence Castle (Food Additives & Contaminants: Part A, 2013)

Determination of phthalate diesters in foods - Emma L. Bradley; Richard A. Burden; Irene Leon; David N. Mortimer; Dennis R. Speck; Laurence Castle (Food Additives & Contaminants: Part A, 2013)

Exploring the sensitivity of the zone of inhibition test for leachable biocides from paper and board food contact materials, and improvements thereof - L. Castle; J. Kelly; S.M. Jickells; S.M. Johns; K.A. Mountfort (Food Additives & Contaminants: Part A, 2012)

Treatment of Selenium in Simulated Refinery Effluent Using a Pilot-Scale Constructed Wetland Treatment System - Michael M. Spacil; John H. Rodgers; James W. Castle; Cynthia L. Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2011)

Coupled energy pathways and the resilience of size-structured food webs - Julia L. Blanchard; Richard Law; Matthew D. Castle; Simon Jennings (Theoretical Ecology, 2011)

Migration of melamine from can coatings cross-linked with melamine-based resins, into food simulants and foods - E.L. Bradley; L. Castle; J.S. Day; J. Leak (Food Additives & Contaminants: Part A, 2011)

Comparison of the migration of melamine from melamine–formaldehyde plastics (‘melaware’) into various food simulants and foods themselves - E.L. Bradley; L. Castle; J.S. Day; I. Ebner; K. Ehlert; R. Helling; S. Koster; J. Leak; K. Pfaff (Food Additives & Contaminants: Part A, 2010)

Determination of polyadipates migrating from lid gaskets of glass jars. Hydrolysis to adipic acid and measurement by LC–MS/MS - M. Driffield; E.L. Bradley; N. Harmer; L. Castle; S. Klump; P. Mottier (Food Additives & Contaminants: Part A, 2010)

Migration of formaldehyde from melamine-ware: UK 2008 survey results - E.L.J. Potter; E.L. Bradley; C.R. Davies; K.A. Barnes; L. Castle (Food Additives & Contaminants: Part A, 2010)

Safety evaluation of food contact paper and board using chemical tests and in vitro bioassays: role of known and unknown substances - U. Honkalampi-Hämäläinen; E.L. Bradley; L. Castle; I. Severin; L. Dahbi; O. Dahlman; J.-C. Lhuguenot; M.A. Andersson; P. Hakulinen; D. Hoornstra; J. Mäki-Paakkanen; M. Salkinoja-Salonen; et al. (Food Additives & Contaminants: Part A, 2010)

Development and single-laboratory validation of an HPLC method for the determination of cyclamate sweetener in foodstuffs - M.J. Scotter; L. Castle; D.P.T. Roberts; R. MacArthur; P.A. Brereton; S.K. Hasnip; N. Katz (Food Additives & Contaminants: Part A, 2009)

New hierarchical classification of food items for the assessment of exposure to packaging migrants: use of hub codes for different food groups - P. Northing; P.K.T. Oldring; L. Castle; P.A.S.S. Mason (Food Additives & Contaminants: Part A, 2009)

Use of overall migration methodology to test for food-contact substances with specific migration limits - E.L. Bradley; L. Castle; S.M. Jickells; K.A. Mountfort; W.A. Read (Food Additives & Contaminants: Part A, 2009)

A sensitive method for the determination of chlorine-36 in foods using accelerator mass spectrometry - M. Baxter; L. Castle; H.M. Crews; M. Rose; C. Garner; G. Lappin; D. Leong (Food Additives & Contaminants: Part A, 2009)

Amino Acid Fluctuations in Young and Old Orange Trees and Their Influence on Glassy-Winged Sharpshooter (Homalodisca vitripennis) Population Densities - J. L. Bi; S. J. Castle; N. C. Toscano (Journal of Chemical Ecology, 2007)

Influence of Seasonal Nitrogen Nutrition Fluctuations in Orange and Lemon Trees on Population Dynamics of the Glassy-Winged Sharpshooter (Homalodisca coagulata) - J. L. Bi; S. J. Castle; F. J. Byrne; S. J. Tuan; N. C. Toscano (Journal of Chemical Ecology, 2005)

Using simple environmental variables to estimate below‐ground productivity in grasslands - R. A. Gill; R. H. Kelly; W. J. Parton; K. A. Day; R. B. Jackson; J. A. Morgan; J. M. O. Scurlock; L. L. Tieszen; J. V. Castle; D. S. Ojima; X. S. Zhang (Global Ecology and Biogeography, 2002)
In many temperate and annual grasslands, above‐ground net primary productivity (NPP) can be estimated by measuring peak above‐ground biomass. Estimates of below‐ground net primary productivity and, consequently, total net primary productivity, are more difficult. We addressed one of the three main objectives of the Global Primary Productivity Data Initiative for grassland systems to develop simple models or algorithms to estimate missing components of total system NPP. Any estimate of below‐ground NPP (BNPP) requires an accounting of total root biomass, the percentage of living biomass and annual turnover of live roots. We derived a relationship using above‐ground peak biomass and mean annual temperature as predictors of below‐ground biomass ( r 2 = 0.54; P = 0.01). The percentage of live material was 0.6, based on published values. We used three different functions to describe root turnover: constant, a direct function of above‐ground biomass, or as a positive exponential relationship with mean annual temperature. We tested the various models against a large database of global grassland NPP and the constant turnover and direct function models were approximately equally descriptive ( r 2 = 0.31 and 0.37), while the exponential function had a stronger correlation with the measured values ( r 2 = 0.40) and had a better fit than the other two models at the productive end of the BNPP gradient. When applied to extensive data we assembled from two grassland sites with reliable estimates of total NPP, the direct function was most effective, especially at lower productivity sites. We provide some caveats for its use in systems that lie at the extremes of the grassland gradient and stress that there are large uncertainties associated with measured and modelled estimates of BNPP.